Features of the development of Scots pine plus tree progenies over a 36-year period in the Zadonetske forestry in Kharkiv region - Терещенко , Л. І.; Лось , С. А.; Губін , Є. А. (Forestry and Forest Melioration, 2023)
Introduction Scots pine (Pinus sylvestris L.) improvement is carried out according to a complex of economic and valuable features: its growth rate; resistance to diseases, pests, and adverse environmental factors; resin productivity; wood quality; volume yield, etc. Therefore, the analysis of the plus tree progenies growth and their development over time will contribute to a better understanding of the hereditary component of phenotype-selected trees and to the improvement of methodical approaches to their evaluation. The aim of the study was to analyze the growth and development dynamics of the offspring of Scots pine plus trees during a 36-year period in the progeny test in the Zadonetske Forestry in the Zmiyiv State Forest Enterprise in Kharkiv region. Materials and Methods The research was carried out in 2021 in the progeny test of the plus trees Scots pine in the Zadonetske Forestry in the Zmiyiv State Forest Enterprise. The progeny test was established by V. V. Mitrochenko in 1986. The plot consists of two parts: full-sib (1.3 ha) and half-sib (0.7 ha). The plant placement scheme for families of full-sib was 1.0 ? 2.5 m, and for half-sib, it was 0.75 ? 2.5 m. The total number of variants was 45 in the full-sib plot and 20 in the half-sib plot. A complete accounting of trees in the variants was carried out along with the determination of growth indicators, quality characteristics, and condition. The growth rate, quality, and condition of the progenies were evaluated in points. The final assessment of variants was carried out based on the sum of points. The progeny vitality was determined as the ratio of the number of living trees at the time of the latest survey to their original number at the time of planting, expressed as a percentage. The correlation analysis was used to compare the approaches to the analysis of the results obtained by the methods of the complete accounting of trees as well as by individual tree sampling. Results According to the criterion of competitive tension, the progeny test at the age of 13 and 36 years did not belong to overcrowded stands. The following dynamics for variant preservation in 3, 13, and 36 years at the sib site were determined: 74.6%, 50.2%, and 36.7% of the number of planted plants. In the half-sib site, it was 41.1%, 33.4%, and 23.2%, respectively. According to the growth indicators of variants, some domination of half-sibs at the age of 13 was noted, which was leveled later. The growth rate for most of the progenies at the age of 36 years was at the control level; however, in height, the proportion of families with higher scores in the full-sib plot was 36%, and for half-sib, it was 21%, at that, for diameter they were 29% and 54%, respectively. The correlation analysis of the elevation rates of 36-year-old trees and these particular trees at the age of 13 (the individual tree sampling), compared to complete accounting (all available trees at the age of 13), showed a stronger hereditary conditionality of the trait. In particular, in the first case, r = 0.49 / 0.85 (half-sib/sib plots), in the second case this index made 0.39 / 0.52. For diameters, this dependence was weak and very weak. According to the results of the comprehensive assessment on the site of sibs, one progeny fell into the group of unpromising for the creation of highly productive and sustainable plantations, and the rest of the progenies were included in the group of relatively promising ones (at the level of control). On the site of half-sibs, one progeny is assigned to the group of promising, and the rest are recognized as relatively promising. Almost every second tree at the age of 13 was classified as minus, later the proportion of minus trees decreased by 2.4 times. A selection by qualitative characteristics at a young age turned out to be more effective than that done by quantitative characteristics. Conclusions The safety of trees on the full-sib plot of the progeny test at 36 years old remained better (36.7%) than that on the half-sib plot (23.2%) due to a sparser seedlings placement. The differentiation of the progenies according to growth indicators at the age of 13 was greater than at the age of 36. Most of the progenies at 36 years grew at the control level, but the proportion of families with higher points than control in the sib plot was 15% higher (36%) in height, and 25% less (29%) in diameter than in the half-sib plot. At the age of 36, the percentage of minus trees in the variants decreased by 2.4 times. At the age of 36, the selection based on qualitative indicators turned out to be more effective than that based on growth indicators. Promising plus trees have been detected. 5 Figs., 4 Tables, 17 Refs.